2005
DOI: 10.1160/th04-03-0189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of perioperative fatal pulmonary embolism and death in cancer surgical patients

Abstract: Cancer patients undergoing surgery are at a high risk of venous thromboembolism, but few studies have described the rate of autopsy-confirmed fatal pulmonary embolism after heparin thromboprophylaxis. In a post hoc analysis of a randomized study (MC-4), which compared the efficacy and safety of certoparin (3000 anti-Xa IU, subcutaneously, once-daily) with unfractionated heparin (5000 IU, subcutaneously, three-times daily) in 23078 patients undergoing surgery lasting more than 30 min, the incidence of autopsy-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 18 publications
1
57
0
4
Order By: Relevance
“…(8) Among cancer patients, VTE is one of the most common complications, patients who are hospitalized and patients who are receiving chemotherapy being at higher risk, (9) as are postsurgical patients. (10) Regarding surgical patients, there is, in addition to clinical risk of VTE, the risk related to the type of surgery these patients are undergoing. This becomes important because surgical risk of venous thromboembolic events is low in outpatient procedures and minimally invasive procedures, whereas it is higher in major surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(8) Among cancer patients, VTE is one of the most common complications, patients who are hospitalized and patients who are receiving chemotherapy being at higher risk, (9) as are postsurgical patients. (10) Regarding surgical patients, there is, in addition to clinical risk of VTE, the risk related to the type of surgery these patients are undergoing. This becomes important because surgical risk of venous thromboembolic events is low in outpatient procedures and minimally invasive procedures, whereas it is higher in major surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…(14) Cancer patients undergoing surgical procedures have a two times higher risk of DVT and a three times higher risk of PTE than do patients without cancer undergoing similar procedures. (10) There is evidence that primary prophylaxis substantially reduces the incidence of VTE without increasing the risk of major bleeding. (1,7) In one meta-analysis, (15) the use of prophylaxis with unfractionated heparin (UFH) in medical inpatients reduced the number of cases of fatal PTE by 64%, that of symptomatic PTE by 58%, and that of symptomatic DVT by 53%.…”
mentioning
confidence: 99%
“…В условиях подобной эндогенной гиперкоагуляции внешние факторы, включая лечебные воздействия, спо-собны критично повлиять на сдвиг гомеостаза. Зарубежные исследователи сообщают о риске ВТЭО на фоне радио-и химиотерапии, включая ее относительно облегченный амбулаторный вариант [12][13][14].…”
Section: актуальность темыunclassified
“…Surgical interventions, both elective and emergency, increase VTE risk in cancer patients compared to similar interventions in non-cancer patients (Gallus, 1997;Kakkar et al, 2005;White et al, 2003;). Despite the utilization of VTE prophylaxis, one multicenter prospective study showed that VTE was the most frequent cause of 30-day mortality in cancer patients undergoing surgical procedures (Agnelli et al, 2006).…”
Section: Vte Prophylaxis In Cancer Patients Undergoing Surgerymentioning
confidence: 99%
“…The issue of extended out-of-hospital prophylaxis in high risk surgical patients was addressed in major clinical trials (Gallus, 1997;Kakkar et al, 2005). In one double-blind, multicenter trial (ENOXACAN II), 322 patients undergoing planned curative open surgery for abdominal or pelvic cancer received enoxaparin (40 mg subcutaneously) daily for 6 to 10 days and were then randomly assigned to receive either enoxaparin (at the same dose) or placebo for another 21 days.…”
Section: Vte Prophylaxis In Cancer Patients Undergoing Surgerymentioning
confidence: 99%